Information technology analysis of the educational process support with orientation toward employers’ requirements - Исаков, Алексей Сергеевич (Technology audit and production reserves, 2015)
The issue of employers’ requirements consideration, when designing educational programs in the higher education institution is discussed in this article. The main research aim is development of formal conception and analysis of employers’ requirements that will allow to correct educational programs in the higher education institution and to shorten the distance between the students’ academic preparation and the reality of labor-market. For the stated aim achievement it is proposed to realize some appropriate models, methods and information support technique of the educational process in the higher education institution. Some advantages of applying modern information technologies of data collection, extraction and its intellectual analysis are provided regarding employers’ requirements definition. The approach to the graduates’ competence classes definition according to the specified requirements on the basis of the multi-criteria classification method is presented. The proposed approach enables to implement a transition from verbal vacancy requirements description to ordinal competence evaluation scale, formed during the educational process. The research results can be applied for realization of the information technology of the educational process support.